2005
DOI: 10.1007/s10111-005-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of train driver visual strategies

Abstract: Train driving is primarily a visual task; train drivers are required to monitor the dynamic scene visually both outside and inside the train cab. Poor performance on this visual task may lead to errors, such as signals passed at danger. It is therefore important to understand the visual strategies that train drivers employ when monitoring and searching the visual scene for key items, such as signals. Prior to this investigation, a pilot study had already been carried out using an eye tracking technique to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 1 publication
(1 reference statement)
0
18
0
Order By: Relevance
“…The driving process in itself is also more complicated than it seems [27]. Firstly, shifts are often long (up to 12-14 hours) and provide little or no stimuli other than the repetitive process of accelerating and braking the train, opening the door (in case of passenger trains) and waiting for signals.…”
Section: The Specifics Of a Train Driver Jobmentioning
confidence: 99%
See 1 more Smart Citation
“…The driving process in itself is also more complicated than it seems [27]. Firstly, shifts are often long (up to 12-14 hours) and provide little or no stimuli other than the repetitive process of accelerating and braking the train, opening the door (in case of passenger trains) and waiting for signals.…”
Section: The Specifics Of a Train Driver Jobmentioning
confidence: 99%
“…All these requirements stem from the fact that trains are usually very heavy (50 to several thousand times more massive than cars) and often drive at high speeds, which makes for long braking distances and large collision masses and speeds and explains why their consequences are usually very serious. This is also the reason for a very complicated and formalised railway traffic control -the rules of which every driver must know through and through.The driving process in itself is also more complicated than it seems [27]. Firstly, shifts are often long (up to 12-14 hours) and provide little or no stimuli other than the repetitive process of accelerating and braking the train, opening the door (in case of passenger trains) and waiting for signals.…”
mentioning
confidence: 99%
“…The remaining time was spent fixating on railway signage and infrastructure, locations beside the track and signals. Luke et al [3] analyzed the visual behaviors of 86 drivers whilst operating in-service trains, revealing that the color of the signal, the color of the next signal, signal type and signal complexity were important factors affecting these behaviors. Naweed et al [4] examined the tasks and activities of urban passenger-train drivers during daily railway driving in order to understand the nature of the visual demand in their task activities.…”
Section: Introductionmentioning
confidence: 99%
“…After the 2000s, human factors including driver's cognitive characteristics, driving task analysis and its application in cab design began to appear in worldwide literatures. T. Luke et al researched trainman's visual strategies using eye-tracking system and found that signal aspect, preceding signal aspects, signal type and signal complexity affected driver's visual behavior [1].…”
Section: Introductionmentioning
confidence: 99%